Primary Musculoskeletal Hydatid Cyst of the Thigh: Diagnostic and Curative Challenge for an Unusual Localization. Issue 3 (2013) - Argy, Nicolas; Abou Bacar, Ahmed; Boeri, Cyril; Lohmann, Caroline; Pfaff, Alexander W; Hansmann, Yves; Christmann, Daniel; Candolfi, Ermanno; Lefebvre, Nicolas
Abstract : Primary muscular echinococcosis is an uncommon localization of hydatid cysts. The nonspecific clinical presentation and possible post-therapeutic complications lead to problems for the diagnosis of this infection and the support of the patient. The authors describe an unusual case of double hydatid cyst of the vastus intermedius muscle. After a precise preoperative evaluation based on clinical, radiological and biological examinations, a surgical excision by pericystectomy combined with perioperative chemotherapy enabled the authors to treat the patient and to prevent postoperative complications. The diagnostic tools and the treatment of this particular type of echinococcosis are discussed.